The effect of manufacturing defects on the fatigue life of selective laser melted Ti-6Al-4V structures. (July 2020) - Hu, Y.N.; Wu, S.C.; Withers, P.J.; Zhang, J.; Bao, H.Y.X.; Fu, Y.N.; Kang, G.Z.
Abstract: The manufacturing defects introduced by selective laser melting typically lead to lower fatigue strength and a larger variation in fatigue life compared to conventionally manufactured structures. X-ray micro computed tomography (μCT) is used to characterize the porosity and lack of fusion defects in terms of population, morphology, dimension and location. The defect size and location are combined with the NASA/FLACGRO (NASGRO) fatigue crack growth model to predict the likely fatigue life, in which an effective initial crack length is defined using the cyclic plastic zone and the defect radius. An eXtended defect zone (XDZ) describing the propensity for local plasticity during fatigue around a defect has been shown through numerical analysis to be a good indicator of the ranking of the threat to fatigue caused by differently located manufacturing defects. This indicates that the effect of a defect, initial radius, r 0, is likely to be pronounced when its center is within 2 r 0 of the surface and maximal when it lies just beneath the surface. Graphical abstract: Unlabelled Image Highlights: The manufacturing defect population has been characterized by synchrotron radiation X-ray micro computed tomography. This defect distribution is combined with a fatigue crack growth model to estimate the likely fatigue life. When plotted against the stress intensity factor arising from the critical defect, the scatter in fatigue life is reduced. Higher fatigue resistance is found for the specimens with cracks initiating from internal defects, as against surface ones.